Anticipatory prescribing in end-of-life care - Wilson, Eleanor; Seymour, Jane E.; Morbey, Hazel; Payne, Sheila; Brown, Jayne; Seale, Clive (EMAP, 2014)
Anticipatory prescriptions are often issued by GPs for patients nearing the end of life, ahead of symptoms they may experience. These prescriptions are often activated by nurses. This article summarises a study investigating nurses’ experiences of using anticipatory prescriptions.